Corporate governance in peruvian companies: breaking the myth of public corporations - Vigil Oliveros, Enrique (2018)
This article develops the legal nature of corporations by establishing that their nature is dual and complementary, how their evolution has been, the types of corporations and their regulatory treatment. The author does not share the idea that our corporations are different from the rest of the world, points out that our legal system is a copy of European civil law, however, it could be thought that the idiosyncrasy of our society can influence corporations, maintains that there is another wrong idea that Peruvians can not have self-regulation in our acts as if they can have foreigners and we commit unlawful acts or frauds to companies that in other latitudes could not even imagine. It concludes by stating that, in the national legal system, our General Corporations Law sets out the corporate types, but unfortunately corporate malpractice allows that, in the Notaries, only limited companies or limited liability companies are constituted. There are no constitutions, for example, partnerships, partnerships.